Development of an Encyclopedia of Traditional Foods Preserved by the Malay Tribe of Kayong Utara Regency as a Biology Learning Resource - Linda Lestari; Mahwar Qurbaniah; Anandita Eka Setiadi (Postgraduate, University of Mataram, 2024)
The local potential of traditional preserved foods of the Malay community of Kayong Utara district can be developed into meaningful learning media. This study aims to analyse the validity and student response to the encyclopedia learning media developed. The research used the Research & Development method with the ADDIE development model. The research stages include Analysis, Design, Development, Implement and Evaluation. The results showed the validity of the developed media in the aspects of language, material, and media with consecutive scores of 88.66% (very feasible), 95.33% (very feasible), and 99.33% (very feasible). Student responses were positive on the results of small-scale and large-scale trials with scores of 87.26% and 88.55% respectively. It is concluded that the encyclopedia of traditional food preserved by the Malay tribe of Kayong Utara Regency is feasible to use and gets a positive response to be used as a biology learning resource.